Does GRACE see the terrestrial water cycle "intensifying"?. Issue 2 (26th January 2016) - Eicker, Annette; Forootan, Ehsan; Springer, Anne; Longuevergne, Laurent; Kusche, Jürgen
Abstract: Several researchers have postulated that, under a changing climate due to anthropogenic forcing, an intensification of the water cycle is already under way. This is usually related to increases in hydrological fluxes as precipitation (P), evapotranspiration (E), and river discharge (R). It is under debate, however, whether such observed or reconstructed flux changes are real and on what scales. Large‐scale increase or decrease of the flux deficit (P‐E‐R), i.e., flux changes that do not compensate, would lead to acceleration or deceleration of water storage anomalies potentially visible in Gravity Recovery and Climate Experiment (GRACE) data. In agreement with earlier studies, we do find such accelerations in global maps of gridded GRACE water storage anomalies over 2003–2012. However, these have been generally associated with interannual and decadal climate variability. Yet we show that even after carefully isolating and removing the contribution of El Niño that partially masks long‐term changes, using a new method, accelerations of up to 12 mm/yr 2 remain in regions such as Australia, Turkey, and Northern India. We repeat our analysis with flux fields from two global atmospheric reanalyses that include land surface models (ERA‐Interim and MERRA‐Land). While agreeing well with GRACE on shorter time scales, they fall short in displaying long‐term trends corresponding to GRACE accelerations. We hypothesize that this may be due to time‐varying biases in the reanalysis fluxes as noticed in other studies. We conclude that even though its data record is short, GRACE provides new information that should be used to constrain future reanalyses toward a better representation of long‐term water cycle evolution. Key Points: A new method for removing ENSO‐related interannual variability is presented GRACE sees regions of distinct water storage acceleration, even after removing an "ENSO" mode Atmospheric‐land surface reanalyses largely fail to reproduce corresponding flux trends